Oscillation of Third-Order Neutral Delay Differential Equations - Tongxing Li; Chenghui Zhang; Guojing Xing (Abstract and Applied Analysis)
The purpose of this paper is to examine oscillatory properties of the third-order neutral delay differential equation [a(t)(b(t)(x(t)+p(t)x(σ(t)))′)′]′+q(t)x(τ(t))=0. Some oscillatory and asymptotic criteria are presented. These criteria improve and complement those results in the literature. Moreover, some examples are given to illustrate the main results.